Leveraging Waqf Land for Enhancing Food Security Initiatives: Best Practices and Strategic Recommendations - Yusoff, Rahmawati Mohd; Kader, Sharifah Zubaidah Syed Abdul; Arshad, Azhani; Halim, Akmal Hidayah; Rosli, Mohd Rilizam; Baharudin, Mohammad Hidir; Mohd Hafiz, Siti Mahfudzoh (AIBPM Publisher, 2024)
Malaysia's population, estimated at 33.7 million in 2023, continues to grow with an annual population growth rate of 0.2 per cent, thus increasing the need for robust food security measures. Despite this, the country struggles with self-sufficiency in basic food production, heavily relying on imports, which resulted in a food trade deficit increased to RM31 billion in 2022 compared to RM25 billion deficit in 2021. Conversely, waqf, an Islamic endowment, presents a unique opportunity for wealth distribution and societal benefit. However, current governance practices in waqf institutions suffer from inadequate management, transparency, and skilled human resources, resulting in the proliferation of idle waqf lands. If effectively strategized, these lands could be optimally utilized for national food security initiatives in Malaysia. This study aims to explore successful global best practices in maximizing waqf land for food security. Examples are including legal reforms to harmonize the regulatory framework governing waqf properties, adopting more flexible and innovative financial models such as PPPs, cash waqf and corporate waqf, through community involvement, using of modern technology and innovative farming techniques such as Geographic Information Systems (GIS), blockchain, and precision agriculture, and so on. The research adopts a qualitative approach, analyzing primary and secondary materials through governing statutes, reported cases, semi-structured interviews, and data from respective administrative bodies. Aligning with national policies like the Shared Prosperity Vision 2030 and the National Agrofood Policy 2.0, this study aims to provide best practices and lessons learned, as well as recommendations for legal frameworks, strategies, policies, and guidelines to enhance sustainable agriculture and community welfare. The ultimate goal is to ensure a secure and sustainable food supply in Malaysia